Structure analysis and anti-fatigue activity of a polysaccharide from Lepidium meyenii Walp. Issue 17 (2nd September 2019) - Tang, Yun; Zhu, Zhen-Yuan; Pan, Li-Chao; Sun, Huiqing; Song, Qiao-Ying; Zhang, Yongmin
Abstract: A polysaccharide was obtained from Lepidium meyenii Walp by hot water extraction and purification by Millipore (100 kD) and Sephadex G-200. The content of polysaccharide was examined to be 89.9% with phenol-sulfuric acid method. Its average molecular weight was estimated to be 2.213 × 10 6 Da by High Performance Gel Permeation Chromatography (HPGPC). Monosaccharide analysis showed that the polysaccharide was composed of arabinose, mannose, glucose and galactose with the molar ratio of 2.134: 1: 2.78: 2.82. After Smith degradation, methylation, infrared spectroscopy and NMR, the primary structure of the polysaccharide was identified. The backbone of the polysaccharide was composed of →4)-β-D-Gal p -(1→ and →4)-α-D-Gal p -(1→, while the branches were comprised of →6)-β-D-Glu p -(1→, →5)- β-D-Ara f -(1→, →3, 6)-α-D-Man p -(1→, →3)-α-D-Gal p -(1→, and α-D-Glu p -(1→. The anti-fatigue effect of the polysaccharide was evaluated using exhaustive swimming test and biochemical indexes. The results indicated the polysaccharide has anti-fatigue effect. Abstract :